Orchid conservation: where do we go from here? - Seaton, Phillip (Lankesteriana: International Journal on Orchidology, 2015)
Faced with such a multitude of threats to the natural world, it is all-too-easy to become despondent. Yet the orchid community in general is becoming much more aware of the problems and, increasingly prepared to take action. Thus, the purpose of this paper is to focus on what can and is being done to conserve orchids.